UPAYA MENINGKATKAN HASIL BELAJAR MUATAN IPS TEMA 9 SUB TEMA 2 MELALUI MODEL PROBLEM BASE LEARNING SISWA KELAS V SDN 14 ULAKAN TAPAKIS - Sanjaya, Wiwit (Dharmas Education Journal (DE_Journal), 2023)
Learning activities are the overall educational process in which there are stages of interaction between educators and students who are interconnected in the continuity of the learning process. To become an educator it is not enough just to have extensive knowledge, but in transferring this knowledge requires proper and correct interaction. The purpose of this research is to describe how the thematic learning outcomes are increased by using the PBL model in Class V SDN 14 Ulakan Tapakis. This type of research was classroom action research, while the research subjects were fifth grade students at SDN 14 Ulakan Tapakis, totaling 20 people consisting of 11 female students and 9 male students. The results showed that the results of observations could be seen from the teacher's aspect, namely 78.57% in cycle I increased to 94.63% in cycle II. Meanwhile, from the perspective of students, 80.35% in cycle I increased to 94.63% in cycle II. then the researcher can conclude that the use of the PBL model in integrated thematic learning can improve student learning outcomes.